2013
DOI: 10.4269/ajtmh.2012.12-0496
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Locally-Produced, Ceramic Cookstoves on Respiratory Disease in Children in Rural Western Kenya

Abstract: Abstract. Household air pollution is a risk factor for pneumonia, the leading cause of death among children 5 years of age. From 2008 to 2010, a Kenyan organization sold~2,500 ceramic cookstoves (upesi jiko) that produce less visible household smoke than 3-stone firepits. During a year-long observational study, we made 25 biweekly visits to 200 homes to determine stove use and observe signs of acute respiratory infection in children 3 years of age. Reported stove use included 3-stone firepit only (81.8%), upes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The study found no evidence that an intervention comprising cleaner burning biomass-fuelled cookstoves reduced the risk of pneumonia in young children [ 67 ]. Similar results have been noted from other African cookstove intervention studies from Kenya [ 63 ] and Rwanda [ 63 ]. In both these studies, the most likely factor was the uptake and sustained use of the cookstove intervention.…”
Section: Impact Of Interventions To Reduce Air Pollutionsupporting
confidence: 90%
“…The study found no evidence that an intervention comprising cleaner burning biomass-fuelled cookstoves reduced the risk of pneumonia in young children [ 67 ]. Similar results have been noted from other African cookstove intervention studies from Kenya [ 63 ] and Rwanda [ 63 ]. In both these studies, the most likely factor was the uptake and sustained use of the cookstove intervention.…”
Section: Impact Of Interventions To Reduce Air Pollutionsupporting
confidence: 90%
“…Overall, findings from the longitudinal observational studies suggest that improved cookstoves are associated with reductions in adverse respiratory health outcomes: one study found significant reductions in paediatric pneumonia and severe pneumonia67; two of three studies that evaluated chronic respiratory diseases found statistically significant decreases among improved stove users57 61 64; three out of six studies found significant improvements in lung function51 64 65 and four out of six studies found significant decreases in self-reported respiratory symptoms 58 65–67. Additionally, these studies provide evidence that improved cookstoves reduce HAP levels: 12 out of 17 studies found that improved cookstoves were associated with significantly decreased kitchen levels of PM pollutants,46 47 49 53 54 59 62 63 69–71 73 and 13 out of 17 studies found significant decreases in indoor CO levels among improved cookstove users 45–47 49 50 54 59 60 63 69–71 73.…”
Section: Resultsmentioning
confidence: 99%
“…Reduction of exposure to important pollutants, like smoke from cooking fires inside the home [46], is being addressed through research studies supported by the Global Alliance for Clean Cookstoves, including in western Kenya [54], [55]. The age of death for some neoplasms, such as female breast cancers, is young; in our study population women died at a median age of 41y (IQR 31–47), with 85% of deaths reported among females <65y.…”
Section: Discussionmentioning
confidence: 98%